Psychostimulant Effect of the Synthetic Cannabinoid JWH-018 and AKB48: Behavioral, Neurochemical, and Dopamine Transporter Scan Imaging Studies in Mice - Ossato, Andrea; Uccelli, Licia; Bilel, Sabrine; Canazza, Isabella; Di Domenico, Giovanni; Pasquali, Micol; Pupillo, Gaia; De Luca, Maria Antonietta; Boschi, Alessandra; Vincenzi, Fabrizio; Rimondo, Claudia; Beggiato, Sarah; et al. (Frontiers in Psychiatry, 2017)
JWH-018 and AKB48 are two synthetic cannabinoids (SCBs) belonging to different structural classes and illegally marketed as incense, herbal preparations or chemical supply for theirs psychoactive cannabis-like effects. Clinical reports from emergency room reported psychomotor agitation as one of the more often observed effects in people assuming SCBs. The present study was aimed to investigate the psychostimulant effect of JWH-018 and AKB48 in male CD-1 mice and to compare their effects with those caused by the administration of cocaine and amphetamine. In vivo studies showed that JWH-018, AKB48, as cocaine and amphetamine, facilitated spontaneous locomotion in mice and their effects were prevented by CB1 receptor blockade and dopamine D1/5 and D2/3 receptors inhibition. SPECT-CT studies on dopamine transporter (DAT) revealed that JWH-018 and AKB48 decreased the [123I]-FP-CIT binding in the striatum of mice, in a similar manner to cocaine and amphetamine. Conversely, in vitro competition binding on mouse and human DAT revealed that, unlike cocaine and amphetamine, JWH-018 and AKB48 did not bind to DAT. Moreover, microdialysis study showed that systemic administration of JWH-018, AKB48, cocaine and amphetamine stimulated dopamine release in the nucleus accumbens shell of freely moving mice. Finally, unlike amphetamine and cocaine, JWH-018 and AKB48 did not induce any changes on spontaneous [3H]-DA efflux from murine striatal synaptosomes. The present results indicate that SCBs could facilitate striatal dopamine release with different mechanisms respect to those of cocaine and amphetamine. Furthermore, they demonstrate, for the first time, that JWH-018 and AKB48 induce a psychostimulant effect in mice possibly related to the facilitation of Nucleus Accumbens dopamine release induced by the two compounds. These data, according to clinical reports, outline the potential psychostimulant action of SCBs highlighting their dangerousness on human health.